2011
DOI: 10.1038/ki.2011.225
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, management, and prognosis of HNF1B nephropathy in adulthood

Abstract: Mutations in HNF1B are responsible for a dominantly inherited disease with renal and nonrenal consequences, including maturity-onset diabetes of the young (MODY) type 5. While HNF1B nephropathy is typically responsible for bilateral renal cystic hypodysplasia in childhood, the adult phenotype is poorly described. To help define this we evaluated the clinical presentation, imaging findings, genetic changes, and disease progression in 27 adults from 20 families with HNF1B nephropathy. Whole-gene deletion was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
223
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(238 citation statements)
references
References 39 publications
(86 reference statements)
12
223
0
3
Order By: Relevance
“…12 Renal phenotype appeared to be extremely heterogenic, with 62% of patients having one or more renal cysts. These cysts may be apparent on a renal ultrasound, mostly in the cortex, but they sometimes require magnetic resonance imaging to be detected.…”
Section: Hnf1b-associated Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…12 Renal phenotype appeared to be extremely heterogenic, with 62% of patients having one or more renal cysts. These cysts may be apparent on a renal ultrasound, mostly in the cortex, but they sometimes require magnetic resonance imaging to be detected.…”
Section: Hnf1b-associated Kidney Diseasementioning
confidence: 99%
“…15 Faguer et al reported a renal function decline of 22.45 ml/min per 1.73 m 2 per year over a median followup of 5.5 years in their cohort of HNF1b patients. 12 About 13%-15% of patients eventually develop ESRD. 16 In a retrospective study of 377 patients with HNF1b mutations, no correlation was found between the type and location of the genetic mutation and severity of kidney failure.…”
Section: Hnf1b-associated Kidney Diseasementioning
confidence: 99%
“…1,2 Hypomagnesemia (plasma Mg 2+ levels,0.7 mmol/L) with hypermagnesuria affects up to 50% of the HNF1B patients. 1,3 In adult kidney, HNF1B is expressed in epithelial cells along all segments of the nephron. The role of HNF1B in renal Mg 2+ handling was, however, pinpointed to the distal convoluted tubule (DCT), where the final urinary Mg 2+ excretion is determined.…”
mentioning
confidence: 99%
“…To date, 47 individuals have been reported with liver disease associated with HNF1β gene defects, 25 as case reports [6,[8][9][10][11][12][13][14] and 22 identified in patients with the known renal disease being screened for HNF1β defects [15][16][17]. Liver involvement may present as cholestasis, elevated liver enzyme levels (ALT and/or GGT), hepatomegaly, or steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably an over-representation as these patients had known liver disease and were subsequently found to harbor a defect in HNF1β. When searching for hepatic injury in patients with known HNF1β defects, the percentages are lower, ranging from 17% to 56% for GGT and 12% to 56% for ALT [14][15][16][17][18]. The degree of enzyme elevation varies from mild (twice the upper limit of normal) to severe (10-times the upper limit CASE REPORT of normal).…”
Section: Case Reportmentioning
confidence: 99%